Alkaline dry cell batteries

By using aromatic carboxylic acid and tin powder in the negative electrode of the alkaline dry battery, the specific surface area of ​​zinc is increased, and the corrosion and re-precipitation of zinc is promoted, which solves the problem of hydrogen caused by incorrect use, prevents the leakage of electrolyte, and improves the battery safety and discharge performance.

CN115280548BActive Publication Date: 2024-12-13PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202080098527.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-18
Filing Date
2020-12-08
Publication Date
2024-12-13
Estimated Expiration
2040-12-08

AI Technical Summary

Technical Problem

The alkaline dry battery caused the reduction of zinc ions due to incorrect use, the zinc ions in the electrolyte decrease, and the resistance increases, resulting in the early reaching of the hydrogen evolution potential, the hydrogen production volume increases, the safety valve works, and the alkaline electrolyte leaks, which is difficult to effectively deal with in the existing technology. .

Method used

The negative electrode of the alkaline dry battery is added as additives. The specific surface area of ​​zinc is increased by the tin powder, and the corrosion and re-precipitation of zinc are promoted, ZnO is formed, dissolved in the electrolyte, maintain the negative electrode potential, and suppress hydrogen gas produce.

Benefits of technology

It effectively suppresses the production of hydrogen caused by incorrect use, prevents the leakage of alkaline electrolyte, and improves the safety and discharge performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115280548B_ABST
    Figure CN115280548B_ABST
Patent Text Reader

Abstract

Alkaline dry batteries include a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an alkaline electrolyte contained in the positive electrode, the negative electrode, and the separator. The negative electrode contains a negative electrode active material containing zinc and an additive, and the additive contains an aromatic carboxylic acid and tin powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an improvement in a negative electrode of an alkaline dry cell. Background Art

[0002] Compared with manganese dry batteries, alkaline dry batteries (alkaline manganese dry batteries) have a larger capacity and can take out a large current, so they are widely used. Alkaline dry batteries have: a positive electrode, a negative electrode, a separator arranged between the positive electrode and the negative electrode, and an alkaline electrolyte contained in the positive electrode, the negative electrode and the separator. The negative electrode contains: a negative electrode active material containing zinc.

[0003] When a plurality of alkaline dry batteries are connected in series to use a device, one of them is sometimes connected and charged with the positive and negative connected in the wrong direction. In addition, the alkaline dry batteries as primary batteries are sometimes mistakenly loaded into a charger for secondary batteries and charged.

[0004] When alkaline dry batteries are charged due to improper use, hydrogen gas is generated inside the battery, and the internal pressure of the battery increases. When the amount of hydrogen gas generated increases and the internal pressure of the battery reaches a specified value, the safety valve operates and the hydrogen gas inside the battery is released to the outside. At this time, while the hydrogen gas is released to the outside, the alkaline electrolyte leaks to the outside, and the equipment may malfunction due to the alkaline electrolyte leaking to the outside.

[0005] Patent document 1 proposes a single-tri-type alkaline battery, characterized in that zinc is used as the main active material of the negative electrode, manganese dioxide or nickel oxyhydroxide is used as the main active material of the positive electrode, a separator formed of a non-woven fabric is used, and a potassium hydroxide aqueous solution is used as an electrolyte, and zinc oxide of 0.08 g or more and 0.1 g or less is added to the battery.

[0006] Patent document 2 proposes an alkaline dry battery, which comprises: a positive electrode, a negative electrode, a separator and an alkaline electrolyte retained by at least the aforementioned separator, wherein the aforementioned negative electrode comprises: a zinc alloy powder as a negative electrode active material, and a gel-like alkaline electrolyte, wherein the aforementioned gel-like alkaline electrolyte comprises a quaternary ammonium salt in an amount of 0.00002M parts by weight (M is the molecular weight of the aforementioned quaternary ammonium salt) or more relative to 100 parts by weight of the aforementioned zinc alloy powder, and the aforementioned alkaline electrolyte and the alkaline electrolyte in the aforementioned gel-like alkaline electrolyte each comprise a zinc compound of 0.3 mol / l or more.

[0007] Patent document 3 proposes an alkaline dry battery, characterized in that it comprises: a positive electrode containing manganese dioxide, a negative electrode containing zinc, a separator disposed between the positive electrode and the negative electrode, and an alkaline electrolyte, wherein the air permeability of the separator is 0.5 to 5.0 ml / sec / cm 2 The potential of the manganese dioxide is 270 to 330 mV (vs. Hg / HgO), and the alkaline electrolyte contains 2.0 to 4.5 wt % of zinc oxide.

[0008] Patent Document 4 proposes an alkaline battery using a caustic alkali aqueous solution as an electrolyte, characterized in that at least one compound selected from aromatic carboxylic acids, substituted derivatives thereof, and salts thereof is added as a preservative for the negative electrode active material.

[0009] Patent document 5 proposes an alkaline battery comprising: a positive electrode, a negative electrode, a separator arranged between the positive electrode and the negative electrode, and an electrolyte contained in the positive electrode, the negative electrode, and the separator, wherein the electrolyte comprises an alkaline aqueous solution, the negative electrode comprises a negative electrode active material comprising zinc and an additive, the additive comprises at least one selected from the group consisting of benzoic acid, phthalic acid, isophthalic acid, and salts thereof, the amount of the negative electrode active material contained in the negative electrode is 176 to 221 parts by mass per 100 parts by mass of water contained in the electrolyte, and the amount of the additive contained in the negative electrode is 0.1 to 1.0 parts by mass per 100 parts by mass of the negative electrode active material.

[0010] Patent document 6 proposes a zinc-alkaline primary battery having a zinc negative electrode, wherein the zinc negative electrode is mainly composed of corrosion-resistant zinc alloy powder that is amalgamated with or without mercury at a content of less than 2 weight %, and a conductive material is mixed therein, wherein the conductive material is granular, fibrous or flaky, and at least its surface is alkali-resistant, easily amalgamated and is formed of a metal or alloy that is more noble than zinc.

[0011] Patent Document 7 proposes an electrochemical cell comprising: an anode containing zinc, an aqueous alkaline electrolyte, a separator, and a cathode containing manganese dioxide, wherein the anode further comprises a conductive metal powder physically mixed with zinc.

[0012] Patent document 8 proposes a gelled negative electrode for an alkaline electrochemical cell, wherein the negative electrode comprises two or more additives selected from the group consisting of zinc-based particles, an alkaline electrolyte, a gelling agent, and an alkali metal hydroxide, an organic phosphate surfactant, a metal oxide, and tin.

[0013] Prior art literature

[0014] Patent Literature

[0015] Patent Document 1: Japanese Patent Application Publication No. 2006-156158

[0016] Patent Document 2: Japanese Patent Application Publication No. 2011-216218

[0017] Patent Document 3: International Publication No. 2010 / 140295

[0018] Patent Document 4: Japanese Patent Application Laid-Open No. 61-208753

[0019] Patent Document 5: International Publication No. 2018 / 163485

[0020] Patent Document 6: Japanese Patent Application Laid-Open No. 61-96665

[0021] Patent Document 7: Japanese Patent Publication No. 2003-502808

[0022] Patent Document 8: Japanese Patent Application No. 2018-514932 Summary of the invention

[0023] If the charging caused by the incorrect use of alkaline dry batteries continues, the zinc precipitation caused by the reduction of zinc ions in the electrolyte in the negative electrode is promoted, and the zinc ions in the electrolyte are reduced. If the zinc ions in the electrolyte are reduced, the resistance of zinc to the precipitation reaction is greatly increased, the negative electrode potential is rapidly reduced, and the hydrogen evolution potential is reached early. As a result, the amount of hydrogen generated increases, and the alkaline electrolyte leaks to the outside while hydrogen is released to the outside due to the operation of the safety valve. In view of this, it is difficult to fully cope with the proposals of patent documents 1 to 3. On the other hand, patent documents 4 to 8 do not provide solutions to the problems caused by the incorrect use of batteries.

[0024] One aspect of the present disclosure relates to an alkaline dry battery, comprising: a positive electrode, a negative electrode, a separator arranged between the positive electrode and the negative electrode, and an alkaline electrolyte contained in the positive electrode, the negative electrode and the separator, wherein the negative electrode contains: a negative electrode active material containing zinc, and an additive, and the additive contains: an aromatic carboxylic acid and tin powder.

[0025] According to the present disclosure, when an alkaline dry battery is charged due to improper use, leakage of an alkaline electrolyte to the outside of the battery can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a front view showing a part of the alkaline dry battery in one embodiment of the present disclosure as a cross section. DETAILED DESCRIPTION

[0027] The alkaline dry battery according to the embodiment of the present disclosure includes a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an alkaline electrolyte (hereinafter simply referred to as electrolyte) contained in the positive electrode, the negative electrode, and the separator.

[0028] The negative electrode contains a negative electrode active material containing zinc and an additive. The additive contains an aromatic carboxylic acid and tin (tin: Sn) powder.

[0029] When alkaline dry batteries are charged due to improper use, the zinc ions (Zn 2+ ) is reduced, resulting in a reaction in which zinc precipitates on the surface of the negative electrode active material. Therefore, the negative electrode potential is maintained at around -1.4V (vs.Hg / HgO), which is the reduction potential of zinc ions. If the charging of the alkaline dry cell is continued, the zinc ions in the electrolyte decrease, the resistance of the zinc to the precipitation reaction increases, and the negative electrode potential decreases to below -1.7V (vs.Hg / HgO), which is the decomposition potential (hydrogen evolution potential) of water in the electrolyte. It should be noted that the zinc ions in the electrolyte are zinc complex ions: Zn(OH) 4 2- exists in the form of.

[0030] On the other hand, by making the negative electrode contain the above-mentioned additives, the cycle of zinc corrosion (formation of ZnO), dissolution of ZnO and re-precipitation of zinc on the surface of the negative electrode active material is accelerated, and the negative electrode potential is maintained near the reduction potential of zinc ions, so that the generation of hydrogen is suppressed, making it less likely to cause the safety valve to operate due to an increase in internal pressure.

[0031] The mechanism of the accelerated cycle of ZnO generation, dissolution, and zinc re-precipitation is unclear, but it is speculated that the tin powder changes the precipitation morphology of charged zinc generated by incorrect use, thereby increasing the specific surface area of ​​zinc. The volume resistivities of Zn and Sn are 5.5μΩcm and 11.5μΩcm, respectively. Compared with Zn, Sn has a higher volume resistivity, so that Zn is preferentially precipitated on the Zn surface. When tin powder is mixed in the negative electrode active material powder containing zinc, the tin powder close to the negative electrode active material blocks a portion of the surface of the negative electrode active material powder. Zinc ions are precipitated by detouring on the surface blocked by the tin powder, so it becomes easy for Zn to grow in a dendritic crystal shape. As a result, the specific surface area of ​​zinc increases.

[0032] The specific surface area of ​​the precipitated zinc increases, so that the reactivity of water and zinc in the electrolyte increases, and a relatively large amount of ZnO is generated on the zinc surface with a large specific surface area. ZnO dissolves in the electrolyte. Aromatic carboxylic acids form complexes with zinc ions in the electrolyte, and therefore play a role in promoting the dissolution of ZnO. The zinc ions released into the electrolyte due to the dissolution of ZnO are re-precipitated on the surface of the negative electrode active material due to charging caused by incorrect use. This cycle continues, so that the negative electrode potential is maintained near the reduction potential of zinc, and the generation of hydrogen caused by the reduction of the negative electrode potential is suppressed.

[0033] Here, aromatic carboxylic acid is a general term for compounds having an aromatic ring and a carboxyl group directly bonded to the aromatic ring. As long as the aromatic carboxylic acid has at least one carboxyl group, it is desirable to have an aromatic polycarboxylic acid with more than two carboxyl groups in order to easily form a stable complex with zinc ions in the electrolyte, wherein aromatic dicarboxylic acids are preferred. At least one carboxyl group possessed by the aromatic carboxylic acid can form a salt. That is, the aromatic carboxylic acid can be an aromatic carboxylate. The cations replaced with H of the COOH group can include alkali metal ions, ions of the second group elements, onium cations, ammonium ions, and the like. As alkali metals, sodium, potassium, and the like can be exemplified. As the second group elements, magnesium, calcium, and the like can be exemplified. The aromatic carboxylic acid can be ionized in the electrolyte and exist as an anion.

[0034] The aromatic ring may be a benzene ring, a naphthalene ring, or a ring other than this, but a benzene ring is preferred. A substituent that does not significantly hinder the formation of a complex with zinc ions may be bonded to the aromatic ring. As aromatic dicarboxylic acids, for example, benzene dicarboxylic acids (i.e., phthalic acids), derivatives of benzene dicarboxylic acids, etc. may be cited. The derivatives contain compounds having substituents (e.g., methyl groups, etc.) other than carboxyl groups bonded to the benzene ring, but do not contain esters. Among phthalic acids, terephthalic acid is particularly preferred in terms of the effect of promoting the dissolution of ZnO. It is expected that more than 90% by mass of the aromatic carboxylic acid is an aromatic dicarboxylic acid, more than 90% by mass of the aromatic dicarboxylic acid is phthalic acids, and more than 90% by mass of the phthalic acids is terephthalic acid.

[0035] The amount of the aromatic carboxylic acid (preferably an aromatic dicarboxylic acid (more preferably terephthalic acid)) contained in the negative electrode can be, for example, 0.05 mass parts or more and 0.5 mass parts or less per 100 mass parts of the negative electrode active material, can be 0.05 mass parts or more and 0.3 mass parts or less, can be 0.08 mass parts or more and 0.2 mass parts or less. In this range, the effect of suppressing the generation of hydrogen during charging caused by incorrect use is sufficiently large. In addition, better discharge performance can be obtained. The aromatic carboxylic acid can be added in advance to the electrolyte used when making the negative electrode. The concentration of the aromatic carboxylic acid in the electrolyte can be, for example, 0.05 mass % or more and 0.5 mass % or less.

[0036] Tin powder has a large hydrogen evolution overvoltage and a specific gravity close to that of zinc. Therefore, it is easy to be evenly dispersed in the negative electrode active material and is not conducive to the discharge reaction of the battery. Therefore, it is suitable as an additive. Tin powder can be a powder with tin in a metallic state as the main component. Tin powder can also be a tin alloy containing trace amounts of other elements, and can also contain trace amounts of tin oxides. Tin powder can be, for example, a powder containing elements other than tin less than 20% by mass and the remainder being metallic tin.

[0037] It should be noted that when a zinc alloy is used as the negative electrode active material, tin may be included in the zinc alloy. However, the tin included in the negative electrode active material as a component of the zinc alloy basically does not have the effect of physically shielding a portion of the surface of the negative electrode active material, and the effect of increasing the specific surface area of ​​zinc cannot be expected. Tin powder is a powder different from the negative electrode active material, and the particles of the negative electrode active material and the tin powder need to be mixed with each other.

[0038] As the negative electrode active material, zinc powder, zinc alloy powder, etc. are used. From the viewpoint of corrosion resistance, the zinc alloy may contain at least one selected from the group consisting of indium, bismuth and aluminum. The indium content in the zinc alloy is, for example, 0.01 to 0.1 mass%. The bismuth content in the zinc alloy is, for example, 0.003 to 0.02 mass%. The aluminum content in the zinc alloy is, for example, 0.001 to 0.03 mass%. From the viewpoint of corrosion resistance, the ratio of elements other than zinc in the zinc alloy is preferably 0.025 to 0.08 mass%.

[0039] The negative electrode active material is usually used in the form of a powder. From the viewpoint of the filling property of the negative electrode and the diffusibility of the electrolyte in the negative electrode, the average particle size (D50) of the negative electrode active material powder is, for example, 100 to 200 μm, preferably 110 to 160 μm. It should be noted that in this specification, the average particle size (D50) refers to the median particle size in the volume-based particle size distribution. The average particle size is obtained, for example, using a laser diffraction / scattering particle distribution measuring device.

[0040] The average particle size (D50) of the tin powder as an additive is preferably smaller than that of the negative electrode active material powder, and can be, for example, 0.1 to 100 μm, or 0.1 to 10 μm. However, the average particle size D50s of the tin powder can be no larger than the average particle size D50z of the negative electrode active material powder. For example, as long as the range of D50s / D50z<1 is satisfied, D50s / D50z<0.1 can be satisfied.

[0041] The amount of tin powder contained in the negative electrode can be, for example, 0.05 mass parts or more and 1 mass parts or less, 0.1 mass parts or more and 0.5 mass parts or less, or 0.2 mass parts or more and 0.4 mass parts or less per 100 mass parts of the negative electrode active material. In this range, the influence on the negative electrode capacity is so small that it can be ignored, and the effect of suppressing hydrogen generation during charging caused by incorrect use is also sufficiently increased.

[0042] From the viewpoint of appropriately controlling the synergistic effect of the aromatic carboxylic acid and the tin powder, the ratio (Mac / Ms) of the mass (Mac) of the aromatic carboxylic acid (preferably phthalic acid) contained in the negative electrode to the mass (Ms) of the tin powder can be set, for example, as 0.05 < Mac / Ms < 10, and can be set as 0.05 < Mac / Ms < 3.

[0043] The positive electrode may contain the above additives. Most of the additives added to the negative electrode remain in the negative electrode, but a small part of the additives contained in the electrolyte in the negative electrode may move to the electrolyte in the positive electrode.

[0044] Examples of the alkaline dry battery according to an embodiment of the present disclosure include a cylindrical battery, a coin-shaped battery, and the like.

[0045] Hereinafter, based on the drawings, the alkaline dry battery of the present embodiment will be described in detail. It should be noted that the present invention is not limited to the following embodiments. In addition, it can be appropriately changed within the range not departing from the scope of exerting the effects of the present invention. Furthermore, it can also be combined with other embodiments.

[0046] Figure 1 FIG. is a front view showing a cross-section of a lateral half of an alkaline dry battery according to an embodiment of the present disclosure. Figure 1 An example of a cylindrical battery having an inside-out structure is shown. As Figure 1 shown, the alkaline dry battery includes: a hollow cylindrical positive electrode 2, a gel-like negative electrode 3 disposed in the hollow portion of the positive electrode 2, a separator 4 disposed between them, and an electrolyte, which are housed in a bottomed cylindrical battery case 1 having a positive terminal. An alkaline aqueous solution is used as the electrolyte.

[0047] The positive electrode 2 is disposed in contact with the inner wall of the battery case 1. The positive electrode 2 contains manganese dioxide and an electrolyte. In the hollow portion of the positive electrode 2, a gel-like negative electrode 3 is filled隔着 the separator 4. The negative electrode 3 generally contains an electrolyte and a gelling agent in addition to a negative electrode active material containing zinc and the above additives.

[0048] The separator 4 is a bottomed cylinder and contains an electrolyte. The separator 4 is composed of a cylindrical separator 4a and a bottom paper 4b. The separator 4a is disposed along the inner surface of the hollow portion of the positive electrode 2 and隔离 the positive electrode 2 and the negative electrode 3. Thus, the separator disposed between the positive electrode and the negative electrode refers to the cylindrical separator 4a. The bottom paper 4b is disposed at the bottom of the hollow portion of the positive electrode 2 and隔离 the negative electrode 3 and the battery case 1.

[0049] The opening of the battery case 1 is sealed by a sealing unit 9. The sealing unit 9 is composed of a gasket 5, a negative terminal plate 7 which also serves as a negative terminal, and a negative current collector 6. The negative current collector 6 is inserted into the negative electrode 3. A safety valve having an annular thin-walled portion 5a is provided on the gasket 5. The negative current collector 6 is in the shape of a nail having a head and a main body, the main body being inserted into a through hole provided in the central cylindrical portion of the gasket 5, and the head of the negative current collector 6 being welded to the flat portion in the central portion of the negative terminal plate 7. The opening end of the battery case 1 is fastened to the flange portion of the peripheral portion of the negative terminal plate 7 through the outer peripheral end of the gasket 5. The outer surface of the battery case 1 is covered with an exterior label 8.

[0050] The following is a detailed description of the alkaline dry battery.

[0051] (negative electrode)

[0052] The negative electrode is obtained by mixing a negative electrode active material containing zinc (powder of zinc, zinc alloy, etc.), an additive (aromatic dicarboxylic acid and tin powder), a gelling agent, and an electrolyte solution.

[0053] The gelling agent is not particularly limited, and for example, a water-absorbing polymer can be used. Examples of the water-absorbing polymer include polyacrylic acid and sodium polyacrylate.

[0054] The amount of the gelling agent contained in the negative electrode is, for example, 0.5 to 2.5 parts by mass per 100 parts by mass of the negative electrode active material.

[0055] In order to adjust the viscosity, etc., a surfactant may be added to the negative electrode. As the surfactant, polyoxyalkylene compounds, phosphoric acid esters, etc. may be mentioned, among which phosphoric acid esters and alkali metal salts thereof are preferred. The surfactant may be added in advance to the electrolyte used when making the negative electrode.

[0056] (Negative electrode current collector)

[0057] The material of the negative electrode current collector inserted into the gel negative electrode includes, for example, metals and alloys. The negative electrode current collector preferably contains copper, and may be made of, for example, an alloy containing copper and zinc, such as brass. The negative electrode current collector may be plated with tin plating or the like as needed.

[0058] (positive electrode)

[0059] The positive electrode generally contains a conductive agent and an electrolyte in addition to manganese dioxide as a positive electrode active material. In addition, the positive electrode may further contain a binder as necessary.

[0060] As manganese dioxide, electrolytic manganese dioxide is preferred. Examples of the crystal structure of manganese dioxide include α-type, β-type, γ-type, δ-type, ε-type, η-type, λ-type, and ramsdellite-type.

[0061] The manganese dioxide is used in the form of powder. From the viewpoint of easily ensuring the filling property of the positive electrode and the diffusibility of the electrolyte in the positive electrode, the average particle size (D50) of the manganese dioxide is, for example, 25 to 60 μm.

[0062] From the viewpoint of moldability and suppression of positive electrode expansion, the BET specific surface area of ​​manganese dioxide may be, for example, 20 to 50 m 2 It should be noted that the BET specific surface area is calculated by measuring the surface area using the BET formula, which is a theoretical formula for multi-molecular layer adsorption. The BET specific surface area can be measured, for example, using a specific surface area measuring device based on a nitrogen adsorption method.

[0063] As the conductive agent, for example, in addition to carbon black such as acetylene black, conductive carbon materials such as graphite can also be mentioned. As graphite, natural graphite, artificial graphite, etc. can be used. The conductive agent can be in a fibrous form, but is preferably in a powdery form. The average particle size (D50) of the conductive agent is, for example, 3 to 20 μm.

[0064] The content of the conductive agent in the positive electrode is, for example, 3 to 10 parts by mass, or preferably 5 to 9 parts by mass, relative to 100 parts by mass of manganese dioxide.

[0065] For alkaline dry batteries, silver or Ag can be added to the positive electrode to absorb the hydrogen generated inside the battery when charging due to improper use. 2 O, AgO, Ag 2 O 3 、AgNiO 2 Silver compounds.

[0066] The positive electrode can be obtained, for example, by press-molding a positive electrode mixture containing a positive electrode active material, a conductive agent, an alkaline electrolyte, and a binder as required into a pellet shape. The positive electrode mixture can be temporarily formed into a flaky or granular shape, classified as required, and then press-molded into a pellet shape.

[0067] After the pellets are housed in the battery case, they can be pressurized a second time using a predetermined tool so that they are in close contact with the inner wall of the battery case.

[0068] (Separator)

[0069] As the material of the separator, for example, cellulose, polyvinyl alcohol, etc. can be exemplified. The separator can be a non-woven fabric using fibers of the above materials as the main body, or a microporous film such as cellophane, polyolefin, etc. A non-woven fabric and a microporous film can be used in combination. As the non-woven fabric, examples can be given: a non-woven fabric obtained by mixing cellulose fibers and polyvinyl alcohol fibers as the main body, a non-woven fabric obtained by mixing rayon fibers and polyvinyl alcohol fibers as the main body, etc.

[0070] Figure 1In the embodiment, a cylindrical separator 4a and a backing paper 4b are used to form a bottomed cylindrical separator 4. The bottomed cylindrical separator is not limited thereto, and any separator of a known shape used in the field of alkaline dry batteries can be used. The separator can be composed of one sheet, or a plurality of sheets can be overlapped if the sheet constituting the separator is thin. The cylindrical separator can be formed by winding a thin sheet multiple times.

[0071] The thickness of the separator is, for example, 200 to 300 μm. The separator preferably has the above thickness as a whole, and if the sheet constituting the separator is thin, a plurality of sheets may be stacked to achieve the above thickness.

[0072] (Electrolyte)

[0073] The electrolyte is contained in the positive electrode, the negative electrode and the separator. As the electrolyte, for example, an alkaline aqueous solution containing potassium hydroxide is used. The concentration of potassium hydroxide in the electrolyte is preferably 20 to 50% by mass. The electrolyte may further contain zinc oxide. The concentration of zinc oxide in the electrolyte is, for example, 1 to 5% by mass.

[0074] From the viewpoint of appropriately controlling the synergistic effect of the aromatic carboxylic acid and the tin powder by the electrolyte, the ratio (Mk / Ms) of the mass (Mk) of KOH contained in the alkaline dry battery (battery cell) to the mass (Ms) of the tin powder contained in the negative electrode can be set to, for example, 20 <Mk / Ms<580。

[0075] (gasket)

[0076] As the material of the gasket, polyamide, polyethylene, polypropylene, etc. can be cited. The gasket is obtained, for example, by injection molding the above materials into a predetermined shape. The gasket usually has a thin-walled portion for explosion-proofing. From the viewpoint of making it easy to break, the thin-walled portion is preferably formed into a ring shape. Figure 1 The gasket 5 has an annular thin-walled portion 5a. From the viewpoint that the thin-walled portion is easily broken when the internal pressure rises, the material of the gasket is preferably 6,10-nylon, 6,12-nylon, and polypropylene.

[0077] (Battery housing)

[0078] For example, a bottomed cylindrical metal case is used as the battery case. For example, a nickel-plated steel plate is used as the metal case. In order to improve the adhesion between the positive electrode and the battery case, it is preferred to use a battery case in which the inner surface of the metal case is covered with a carbon coating.

[0079] Hereinafter, the present invention will be specifically described based on Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0080] <Example 1>

[0081] Follow the steps (1) to (3) below to make Figure 1 The single 3-type cylindrical alkaline dry cell (LR6) shown

[0082] (1) Preparation of positive electrode

[0083] Graphite powder (average particle size (D50) 8 μm) as a conductive agent was added to electrolytic manganese dioxide powder (average particle size (D50) 35 μm) as a positive electrode active material to obtain a mixture. The mass ratio of electrolytic manganese dioxide powder to graphite powder was set to 92.4:7.6. It should be noted that the electrolytic manganese dioxide powder used was a specific surface area of ​​41 m 2 / g. The electrolyte is added to the mixture, stirred thoroughly, and then compressed into flakes to obtain a positive electrode mixture. The mass ratio of the mixture to the electrolyte is set to 100:1.5.

[0084] An alkaline aqueous solution containing potassium hydroxide (concentration: 35 mass %) and zinc oxide (concentration: 2 mass %) was used as the electrolytic solution.

[0085] The flaky positive electrode mixture was pulverized into particles, and 11 g of the obtained particles were classified using a 10-100 mesh sieve and press-molded into a predetermined hollow cylindrical shape with an outer diameter of 13.65 mm to prepare two positive electrode pellets.

[0086] (2) Preparation of negative electrode

[0087] Zinc alloy powder (average particle size (D50) 130 μm) and tin powder (average particle size (D50) 1.5 μm) as negative electrode active materials were mixed with terephthalic acid, an electrolyte and a gelling agent to obtain a gelled negative electrode 3. The electrolyte used was the same as that used for the preparation of the positive electrode.

[0088] As the zinc alloy, a zinc alloy (ZnBiAlIn) containing 0.02 mass % of indium, 0.01 mass % of bismuth, and 0.005 mass % of aluminum was used. As the electrolyte, the same electrolyte as that used in the preparation of the positive electrode was used.

[0089] As the gelling agent, a mixture of cross-linked branched polyacrylic acid and highly cross-linked chain-type sodium polyacrylate is used.

[0090] The amount of tin powder was 0.25 parts by mass per 100 parts by mass of the negative electrode active material. The amount of terephthalic acid was 0.14 parts by mass per 100 parts by mass of the negative electrode active material. The mass ratio of the negative electrode active material to the electrolyte to the gelling agent was 100:50:1.

[0091] (3) Assembly of alkaline dry batteries

[0092] Varniphite manufactured by Nippon Graphite Co., Ltd. is applied to the inner surface of a bottomed cylindrical battery case made of nickel-plated steel plate (outer diameter 13.80 mm, wall thickness of the cylindrical part 0.15 mm, height 50.3 mm) to form a carbon coating with a thickness of about 10 μm, thereby obtaining a battery case 1. After two positive electrode pellets are inserted longitudinally into the battery case 1, they are pressurized to form a positive electrode 2 in a state of being closely attached to the inner wall of the battery case 1. After a bottomed cylindrical separator 4 is arranged on the inner side of the positive electrode 2, the above-mentioned electrolyte is injected and impregnated into the separator 4. It is left in this state for a predetermined time to allow the electrolyte to penetrate from the separator 4 to the positive electrode 2. Thereafter, 6 g of the gel-like negative electrode 3 is filled into the inner side of the separator 4.

[0093] The ratio (Mk / Ms) of the mass (Mk) of KOH contained in the alkaline dry battery (battery cell) to the mass (Ms) of the tin powder contained in the negative electrode was 114.

[0094] The separator 4 is composed of a cylindrical separator 4a and a backing paper 4b. The cylindrical separator 4a and the backing paper 4b are made of a non-woven fabric sheet (weight per unit area 28 g / m2) obtained by mixing rayon fiber and polyvinyl alcohol fiber in a mass ratio of 1:1 as the main body. 2 The thickness of the nonwoven fabric sheet used for the base paper 4b is 0.27 mm. The separator 4a is formed by rolling up a nonwoven fabric sheet having a thickness of 0.09 mm in three layers.

[0095] The negative electrode collector 6 is obtained as follows: After general brass (Cu content: about 65 mass%, Zn content: about 35 mass%) is press-processed into a nail shape, the surface is tin-plated to obtain it. The diameter of the main body of the negative electrode collector 6 is 1.15 mm. The head of the negative electrode collector 6 is welded to the negative terminal plate 7 made of nickel-plated steel plate. After that, the main body of the negative electrode collector 6 is pressed into the through hole in the center of the gasket 5 of the safety valve with a thin wall portion and a polyamide 6,12 as the main component. In this way, a sealing unit 9 formed by the gasket 5, the negative terminal plate 7 and the negative electrode collector 6 is made.

[0096] Next, the sealing unit 9 is set at the opening of the battery case 1. At this time, the main body of the negative electrode collector 6 is inserted into the negative electrode 3. The opening end of the battery case 1 is fastened to the peripheral edge of the negative electrode terminal plate 7 via the gasket 5, and the opening of the battery case 1 is sealed. The outer surface of the battery case 1 is covered with an external label 8. In this way, the alkaline dry battery A1 is manufactured.

[0097] [evaluate]

[0098] The following evaluation test was performed using the battery A1 prepared above: One battery A1 was prepared and connected to a circuit through which a reverse current of 0.1 A was passed, and the presence or absence of battery leakage was examined 60 minutes after the reverse connection was started.

[0099] The above evaluation test was performed five times, and the number of batteries with leakage (leakage number) was calculated.

[0100] It should be noted that the above evaluation test was conducted under the assumption that one battery was mistakenly connected with the positive and negative poles reversed when four batteries were installed in series in a low-load (30Ω) device. The 60-minute charging time was set to take into account the time required for the user to confirm the installation and removal of the battery after discovering abnormal operation of the device after installing the battery in the device.

[0101] <Comparative Example 1>

[0102] An alkaline dry battery B1 was produced and evaluated in the same manner as in Example 1 except that tin powder was not used as an additive in the production of the negative electrode.

[0103] <Comparative Example 2>

[0104] An alkaline dry battery B2 was produced and evaluated in the same manner as in Example 1 except that terephthalic acid was not used as an additive in the production of the negative electrode.

[0105] <Comparative Example 3>

[0106] In the preparation of the negative electrode, tin powder was not used as an additive. For the zinc alloy as the negative electrode active material, a zinc alloy (ZnBiAlInSn) containing 0.02 mass % of indium, 0.01 mass % of bismuth, 0.005 mass % of aluminum and 0.01 mass % of tin was used. Except for this, an alkaline dry battery B3 was prepared and evaluated in the same manner as in Example 1.

[0107] <Comparative Example 4>

[0108] An alkaline dry battery B4 was produced and evaluated in the same manner as in Example 1 except that neither tin powder nor terephthalic acid was used as an additive in the production of the negative electrode.

[0109] Table 1 shows the evaluation results.

[0110] [Table 1]

[0111] Battery Terephthalic acid Metal Sn Negative active material Leakage number A1 Add to Add to ZnBiAIIn 0 / 5 B1 Add to none ZnBiAIIn 4 / 5 B2 none Add to ZnBiAIIn 4 / 5 B3 Add to none ZnBiAIInSn 4 / 5 B4 none none ZnBiAIIn 5 / 5

[0112] In the battery A1 of Example 1 in which terephthalic acid and tin powder were added to the negative electrode, the number of leaks was 0. On the other hand, in Comparative Examples 1 to 4 in which at least one of terephthalic acid and tin powder was not used, leaks were observed in more than 80% of the batteries. In Comparative Example 3, a zinc alloy containing tin was used as the negative electrode active material, but the effect of using tin powder was not observed.

[0113] <Examples 2 to 5>

[0114] In the preparation of the negative electrode, the amount of tin powder per 100 parts by mass of the negative electrode active material was fixed at 0.25 parts by mass, and the amount of terephthalic acid per 100 parts by mass of the negative electrode active material was changed as shown in Table 2. Alkaline dry batteries A2 to A5 were prepared and evaluated in the same manner as in Example 1. The evaluation results are shown in Table 2.

[0115] [Table 2]

[0116]

[0117] <Examples 6 to 9>

[0118] In the preparation of the negative electrode, the amount of terephthalic acid per 100 parts by mass of the negative electrode active material was fixed at 0.14 parts by mass, and the amount of tin powder per 100 parts by mass of the negative electrode active material was changed as shown in Table 3. Alkaline dry batteries A6 to A9 were prepared and evaluated in the same manner as in Example 1. The evaluation results are shown in Table 3.

[0119] [Table 3]

[0120]

[0121] According to Tables 2 and 3, it can be understood that when the amount of tin powder contained in the negative electrode is controlled to be greater than 0.05 mass parts and less than 1 mass part per 100 mass parts of the negative electrode active material, and when the amount of aromatic carboxylic acid contained in the negative electrode is controlled to be greater than 0.05 mass parts and less than 0.5 mass parts per 100 mass parts of the negative electrode active material, no leakage occurs. As can be seen from the above, by using the additive within the above range, the generation of hydrogen can be more effectively suppressed.

[0122] Industrial Applicability

[0123] The embodiments of the present disclosure can be used for all devices (especially low-load devices) that use dry cell batteries as power sources. Examples of low-load devices include radios, clocks, and portable music players.

[0124] Description of Reference Numerals

[0125] 1 Battery housing

[0126] 2 Positive electrode

[0127] 3 Negative electrode

[0128] 4 Cylindrical separator with bottom

[0129] 4a Cylindrical separator

[0130] 4b Backing paper

[0131] 5. Gasket

[0132] 5a Thin wall part

[0133] 6 Negative electrode collector

[0134] 7 Negative terminal plate

[0135] 8 Exterior Labels

[0136] 9 Sealing unit

Claims

1. An alkaline dry battery comprising: a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an alkaline electrolyte contained in the positive electrode, the negative electrode and the separator, The negative electrode comprises: a negative electrode active material containing zinc, and an additive, The additives include: aromatic carboxylic acid and tin powder.

2. The alkaline dry battery according to claim 1, wherein The amount of the tin powder contained in the negative electrode is 0.05 parts by mass or more and 1 part by mass or less per 100 parts by mass of the negative electrode active material.

3. The alkaline dry battery according to claim 1, wherein The amount of the aromatic carboxylic acid contained in the negative electrode is 0.05 parts by mass or more and 0.5 parts by mass or less per 100 parts by mass of the negative electrode active material.

4. The alkaline dry battery according to any one of claims 1 to 3, wherein The aromatic carboxylic acid includes an aromatic dicarboxylic acid.

5. The alkaline dry battery according to claim 4, wherein: The aromatic dicarboxylic acid includes phthalic acid.

6. The alkaline dry battery according to claim 5, wherein The phthalic acid includes terephthalic acid.

Citation Information

Patent Citations

  • Alkaline battery

    JP1986208753A

  • Alkaline battery with improved anode

    JP2003502808A

  • AA type alkaline battery

    JP2006156158A

  • Alkaline dry battery

    JP2011216218A

  • Alkaline dry battery

    WO2010140295A1